Characterization techniques of a shape memory nickel titanium alloy - Andrade, C.A.R. (2020)
This paper presents a characterization processes study of metallic alloys, more specifically the shape memory alloys (SMA) composed by Nickel and Titanium (NiTinol). Two different wire suppliers were studied, starting with metallographic analysis until observe the contours of the grain wires. Differential scanning calorimetry (DSC) test was also performed to obtain phase transformation temperatures of the NiTinol alloys. Finally, after several tensile tests, some results were obtained for stresses, strains, elasticity modules and maximum rupture deformation.